20 years performance measurements of a landfill cover system with components constructed from pre-treated dredged sediments. (December 2019) - Berger, Klaus; Groengroeft, Alexander; Gebert, Julia
Highlights: Mineral liners from pre-treated dredged material may fail in distinct phases. A mineral liner from pre-treated dredged material performed well for 20 years. The design of the entire cover system is important for the liner performance. A "slow" lateral drainage layer keeps the liner surface moist. Hydro-chemical data are helpful for identifying hydrologic processes. Abstract: The water balance and effectiveness of a landfill cover containing a liner from fine-grained dredged material ('METHA-material') and a drainage layer from sandy dredged material ('METHA-sand') from the Port of Hamburg (Northern Germany) was investigated for 20 years using two test fields (lysimeters), each 500 m 2 in size. The layering within the standard design test field (FS) is identical to the layering of the cover on the landfill, whereas the alternative design test field (FA) was designed to provoke desiccation of the liner. The setup abstained from continuous side walls cutting through the liners in order to allow for material properties representative for the landfill cover, at the cost of possible minor lateral inflows or outflows, which were, however, considered negligible. By example of the lysimeter FA the risk of desiccation-induced failure of a liner from METHA-material under the given climate could be shown. In contrast, the discharges and hydro-chemical parameters measured for the lysimeter FS indicate continuous high efficiency of the liner until today. The average discharge below the liner was 14.9 mm/yr. The entire cover contributes to the good liner performance. Reason are (1) the low hydraulic conductivity of the liner (5 × 10 −10 m/s) and its large thickness (1.5 m); (2) the increased stresses on the liner due to the 2.5 m thick overlaying cover; (3) the 1.0 m thick drainage layer from slowly-draining METHA-sand, allowing for a continuous nearly water-saturated fringe above the liner; and (4) the sufficient amount of plant available water in the recultivation layer.